Proposed Novel Eco-Friendly Natural Fiber of Gnetum Gnemon for Military Grade Applications - Bhiftime, Eka Irianto; Dewa, Rando Tungga; Pratomo, Arief Nur (Jurnal Rekayasa Mesin, 2022)
This paper investigates a tensile strength and microstructure characterization of Gnetum gnemon as a newly proposed eco-friendly natural fiber for composites reinforcement. Natural fibers have recently become attractive to researchers, engineers and scientists as an alternative reinforcement for composites. It has relatively low cost, renewable (easily available), and biodegradable. The production system requires simple and energy-efficient equipment and can be exploited as a replacement for the conventional fiber, such as Kevlar for personnel protection. The strength of Gnetum gnemon was found to be comparable with existing new composites. The form of fiber was found to be depended on the lignin, hemicellulose, benzene, and other impurities, thus made it larger and not uniform. These results show great potential as a competitor to the predecessor natural fibers used in composite materials of armor materials, if given special chemical treatment to increase their initial mechanical properties.